2015
DOI: 10.1111/joor.12298
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the larynx and pharynx: effects of age, gender and height revealed by multidetector computed tomography

Abstract: Although oropharyngeal and laryngeal structures are essential for swallowing, the three-dimensional (3D) anatomy is not well understood, due in part to limitations of available measuring techniques. This study uses 3D images acquired by 320-row area detector computed tomography ('320-ADCT'), to measure the pharynx and larynx and to investigate the effects of age, gender and height. Fifty-four healthy volunteers (30 male, 24 female, 23-77 years) underwent one single-phase volume scan (0.35 s) with 320-ADCT duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
4
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 19 publications
3
59
4
2
Order By: Relevance
“…Although we did not stratify patients by their anthropometric features, published reports have noted no significant relationship between pharyngeal length and other anthropometric measures. 1719 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we did not stratify patients by their anthropometric features, published reports have noted no significant relationship between pharyngeal length and other anthropometric measures. 1719 …”
Section: Discussionmentioning
confidence: 99%
“…Another issue that can potentially influence the manometric recordings of the pharynx includes some anthropometric features such as subject height or more precisely the length of the contractile pharynx. Although we did not stratify patients by their anthropometric features, published reports have noted no significant relationship between pharyngeal length and other anthropometric measures [17][18][19]. Although we did not do a formal comparison between young and elderly individuals in terms of the influence of aging on the observed variability of pharyngeal peristaltic pressure amplitude due to inadequate number of those over the age of 70.…”
mentioning
confidence: 91%
“…The larynx position at rest is said to differ between men and women, and similar results were obtained in this study. Inamoto et al found that there was a significant gender difference in the hyoid bone position and laryngeal size when examining the pharynx and larynx in adults . From these things, it was thought that the larynx that remained high was not easily affected by sarcopenia during swallowing.…”
Section: Discussionmentioning
confidence: 99%
“…It's bigger in men than in women [17]. And we think that's why larynx cancer is 6-fold more common in men than women.…”
Section: Discussionmentioning
confidence: 99%